Predation on the lizard Ameiva ameiva (Sauria: Teiidae) by a coral snake Micrurus frontalis (Serpentes: Elapidae) in Brazil. - Maffei, Fabio (2009)
We report a case of elapid predation on a lizard in Brazilian Savannah. A subterranean coral snake (Micrurus frontalis) was found preying a green lizard (Ameiva ameiva) in Southeastern Brazil.